2019
DOI: 10.1002/hep.30519
|View full text |Cite
|
Sign up to set email alerts
|

A Large‐Scale Multicenter Study Validates Aldo‐Keto Reductase Family 1 Member B10 as a Prevalent Serum Marker for Detection of Hepatocellular Carcinoma

Abstract: Aldo‐keto reductase family 1 member B10 (AKR1B10) is a secretory protein overexpressed in hepatocellular carcinoma (HCC). We aimed to evaluate AKR1B10 as a serum marker for detection of HCC. Herein, we conducted a cohort study that consecutively enrolled 1,244 participants from three independent hospitals, including HCC, healthy controls (HCs), benign liver tumors (BLTs), chronic hepatitis B (CHB), and liver cirrhosis (LC). Serum AKR1B10 was tested by time‐resolved fluorescent assays. Data were plotted for rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 46 publications
(99 reference statements)
1
69
0
Order By: Relevance
“…Furthermore, consistent with our results, COL1A1,39 40 42 AKR1B1039 41 and ubiquitin D (UBD)41 42 were among the most upregulated genes in severe disease. While COL1A1 encodes for a major constituent of fibrous tissue during hepatic fibrogenesis (collagen type 1), AKR1B10 is implicated in intracellular metabolism and regulation of intracellular signalling, and it has robustly been implicated in hepatic carcinogenesis 43. UBD encodes for ubiquitin D, which is implicated in the formation of Mallory-Denk bodies during steatohepatitis and is also upregulated in liver cancer 44.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, consistent with our results, COL1A1,39 40 42 AKR1B1039 41 and ubiquitin D (UBD)41 42 were among the most upregulated genes in severe disease. While COL1A1 encodes for a major constituent of fibrous tissue during hepatic fibrogenesis (collagen type 1), AKR1B10 is implicated in intracellular metabolism and regulation of intracellular signalling, and it has robustly been implicated in hepatic carcinogenesis 43. UBD encodes for ubiquitin D, which is implicated in the formation of Mallory-Denk bodies during steatohepatitis and is also upregulated in liver cancer 44.…”
Section: Discussionmentioning
confidence: 99%
“…The N-glycosylated isoform of AFP (AFP-L3), which contains core fucosylation on its N-linked glycans, only exists in HCC but is absent in other liver diseases and therefore can further enhance the specificity of HCC diagnosis. Unfortunately, a quite large proportion of HCC patients have an AFP negative until the laterstage (5,6). In addition, the AFP level has also been associated with pathological grade, progression, and survival HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the concentration of serum AFP varies dramatically with patients. It is known that 30-40% of HCC patients have a AFP level below the detection level of 20 ng/mL in serum, and remain AFP negative until the later-stage (5)(6)(7). Meanwhile, many other studies have also revealed that the high concentration of AFP in patients' serum was associated with high risk of tumor recurrence/progression and reduced survival at different stages of the diseases (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In oral squamous cell carcinoma [9,19], non-small cell lung carcinoma [20] and liver carcinoma [7], high expression levels of AKR1B10 in patients is correlated with poor prognosis. Large-scale and multicenter studies have shown that AKR1B10 may serve as a serological markers for HCC in humans [10]. AKR1B10 plays a critical role in invasion and chemoresistance in BC cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, mRNA levels of AKR1B10 were detected in several types of tumors [7][8][9]. In hepatocellular carcinoma (HCC) patients, the high expression of AKR1B10 positively correlated with poor prognosis [10]. In patients with BC, high expression of AKR1B10 is associated with drug resistance [11].…”
mentioning
confidence: 99%